1993
DOI: 10.1002/ajmg.1320470315
|View full text |Cite
|
Sign up to set email alerts
|

Complex segregation analysis of antibodies to thyroid peroxidase in old order amish families

Abstract: Autoimmune thyroid disease (AITD) may be characterized by the measurement in serum of antibodies to thyroid peroxidase. A population of Old Order Amish individuals and families was investigated to determine the prevalence of these antibodies and to examine hypotheses about the mode of transmission of thyroid antibodies. Complex segregation analyses were performed on 4 large multigenerational Old Order Amish families composed of 26 nuclear families containing 199 first degree relatives. Several alternative hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…36 The genetic susceptibility to the production of thyroid antibodies was further supported by several segregation analyses in families with thyroid antibodies that suggested a Mendelian dominant pattern of inheritance. [37][38][39] Indeed, our results have shown CTLA-4 to be linked with TAbs in a dominant inheritance pattern. In addition, it was recently found that recognition of particular TPO epitopes within the autoantibody immunodominant region may be transmitted within families.…”
Section: Discussionsupporting
confidence: 57%
“…36 The genetic susceptibility to the production of thyroid antibodies was further supported by several segregation analyses in families with thyroid antibodies that suggested a Mendelian dominant pattern of inheritance. [37][38][39] Indeed, our results have shown CTLA-4 to be linked with TAbs in a dominant inheritance pattern. In addition, it was recently found that recognition of particular TPO epitopes within the autoantibody immunodominant region may be transmitted within families.…”
Section: Discussionsupporting
confidence: 57%
“…Until now, there is no segregation analysis performed on AITDs in order to determine transmission mode of inheritance of these diseases independently from disease parameters such as antibodies titres. Thus, two previous studies have reported evidence for genetic transmission of thyroid peroxidase auto antibodies in Old Order Amish families using the Pointer program (Pauls et al 1993;Jaume et al 1999).…”
Section: Discussionmentioning
confidence: 94%
“…A high prevalence of autoimmune thyroid disease, as evidenced by positive thyroid autoantibodies, has been previously observed in Amish families (34). However, autoimmune thyroid disease does not appear to be related to FDH in this family, because its prevalence was not different in subjects with or without FDH.…”
Section: -mentioning
confidence: 66%